Entorno familiar y rendimiento académico de los estudiantes del 5º, 6º y 7º año de la Escuela General Básica 24 de mayo de la Ciudad de Loja, período 2019-2020 y la intervención del Trabajador Social - Chimbo López., Erika Jacqueline (2020)
The present thesis called "Family environment and Academic Performance of the students of the 5th, 6th and 7th year of the General Basic School May 24 of the City of Loja, period 2019-2020 and the Intervention of the Social Worker" Identifying the research problem was raised as objectives; Carry out a diagnosis of the causes of the low academic performance of the students of the General Basic School May 24 of the City of Loja, determine how the family environment affects the academic performance of the students of the General Basic School 24 of May of the City of Loja and design a proposal for social action focused on the problem investigated. With the purpose of strengthening the participation and communication of parents and children of the "General School May 24" of the city of Loja to improve the academic performance of students through different alternatives that allow to sensitize the family in such a way that the Be aware of the importance of participation and communication in the formation of your children, which helps the student to improve their development. For the collection and analysis of the data, a series of methodological processes such as the scientific method were used, supported by auxiliary methods such as: inductive, deductive, analytical and descriptive, including techniques such as direct observation, survey and interview in order to meet the objectives. The main findings found in the research determine that 50% of families have family problems that are mostly caused by lack of communication and parental participation within the educational field, for various reasons such as work, performing household chores or simply because of their children's disinterest. 50% of students have low academic performance due to the aforementioned problems, which involves inappropriate behavior and academic performance of the child. 5 The intervention of the Social Worker is essential within the Educational Field, since within their functions are the prevention, detection of any type of violence and act in the best way on the problem. That is why, from the social work approach, a social action plan called Family and School Together was designed to improve education that is based on strengthening the participation and communication of parents and children of the "General School 24 de Mayo" of the city of Loja to improve the academic performance of students.